Effect of thymoquinone on sepsis-induced cardiac damage via anti-inflammatory and anti-apoptotic mechanisms. Issue 9 (September 2022) - Guo, Wenyan; Long, Xiaofeng; Lv, Mingyi; Deng, Shuling; Liu, Duping; Yang, Qin
Objective: Sepsis is a systemic and deleterious host reaction to severe infection. Cardiac dysfunction is an established serious outcome of multiorgan failure associated with this condition. Therefore, it is important to develop drugs targeting sepsis-induced cardiac damage and inflammation. Thymoquinone (TQ) has anti-inflammatory, anti-oxidant, anti-fibrotic, anti-tumor, and anti-apoptotic effects. This study examined the effects of thymoquinone on sepsis-induced cardiac damage. Methods: Male BALB/c mice were randomly segregated into four groups: control, TQ, cecal ligation and puncture (CLP), and CLP + TQ groups. CLP was performed after gavaging the mice with TQ for 2 weeks. After 48 hours, we estimated the histopathological changes in the cardiac tissue and the serum levels of cardiac troponin-T. We evaluated the expression of factors associated with inflammation, apoptosis, oxidative stress, and the PI3K/AKT pathway. Results: TQ significantly reduced intestinal histological alterations and inhibited the upregulation of interleukin-6, tumor necrosis factor-α, Bax, NOX4, p-PI3K, and p-AKT. TQ also increased Bcl-2, HO-1, and NRF2 expression. Conclusion: These results suggest that TQ effectively modulates pro-inflammatory, apoptotic, oxidative stress, and PI3K/AKT pathways, making it indispensable in the treatment of sepsis-induced cardiac damage.